Environmental Communication, Local Wisdom, and Mitigation of Sampang Flood - Nikmah Suryandari; Qoniah Nur Wijayani (Komunikator, 2021)
The people in Sampang Madura are accustomed to flood disasters so routinely that the people had become accustomed to and fully understood the character of the floods. This study aimed to identify the local wisdom of the Madurese community in dealing with, mitigating, and adapting to disasters, especially floods. The research was conducted in three stages: preparation, observation, in-depth interviews, and data analysis. The preparation stage was carried out by collecting secondary data about Sampang geography, the disaster histories, and people tradition and custom. In the second phase, in-depth interviews were carried out with the Sampang community and BPBD about how people deal with and adapt to disasters. The third stage was data analysis. The result showed that the people of Sampang had strong belief in their ancestral heritage, that everything comes from God, so they have to face it. People carried out disaster mitigation and adaptation by checking for early signs of disaster and following the advice. Besides, they were always connected with their relatives in other areas who gave early indications of flooding. Moreover, they built houses adaptive to flood. The people of Sampang can face, mitigate, and adapt to natural disasters in their area with confidence, knowledge, and following the advice.